Gbvdr6, a Gene Encoding a Receptor-Like Protein of Cotton (Gossypium barbadense), Confers Resistance to Verticillium Wilt in Arabidopsis and Upland Cotton - Yang, Yuwen; Chen, Tianzi; Ling, Xitie; Ma, Zhengqiang (Frontiers in Plant Science, 2018)
Verticillium wilt is a soil-borne disease that can cause devastating losses in cotton production. Because there is no effective chemical means to combat the disease, the only effective way to control Verticillium wilt is through genetic improvement. Therefore, the identification of additional disease-resistance genes will benefit efforts towards the genetic improvement of cotton resistance to Verticillium wilt. Based on screening of a BAC library with a partial Ve homologous fragment and expression analysis, a V. dahliae-induced gene, Gbvdr6, was isolated and cloned from the Verticillium wilt-resistant cotton G. barbadense cultivar Hai7124. The gene was located in the gene cluster containing Gbve1 and Gbvdr5 and adjacent to the Verticillium wilt-resistance QTL hotspot. Gbvdr6 was induced by Verticillium dahliae Kleb and by the plant hormones salicylic acid (SA), methyl jasmonate (MeJA) and ethephon (ETH) but not by abscisic acid (ABA). Gbvdr6 was localized to the plasma membrane. Overexpression of Gbvdr6 in Arabidopsis and cotton enhanced resistance to V. dahliae. Moreover, the JA/ET signaling pathway-related genes PR3, PDF 1.2, ERF1 and the SA-related genes PR1 and PR2 were constitutively expressed in transgenic plants. Gbvdr6-overexpressing Arabidopsis was less sensitive than the wild-type plant to MeJA. Furthermore, the accumulation of reactive oxygen species and callose was triggered at early time points after V. dahliae infection. These results suggest that Gbvdr6 confers resistance to V. dahliae through regulation of the JA/ET and SA signaling pathways.